MAPPING THE DISTRIBUTION OF SALTWATER CROCODILE (Crocodylus porosus) AND RISKS OF HUMAN-CROCODILE CONFLICTS IN SETTLEMENTS AROUND KUTAI NATIONAL PARK, EAST KALIMANTAN - Ramdani Manurung; Mirza Dikari Kusrini; Lilik Budi Prasetyo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2021)
Human-crocodile conflicts (HCC) are problems affecting crocodile conservation. Scientific publications on crocodile attack cases in Indonesia are few with low validation which hinder optimal conflict mitigation efforts. The estuarine river of Kutai National Park is a natural habitat for saltwater crocodiles and mostly nearby dense settlements. This study aims to map the distribution of saltwater crocodiles and potential conflicts in the Kutai National Park area. To predict the distribution of saltwater crocodiles, we used Maximum Entropy MAXENT with its environmental predictors i.e. slope, altitude, distance from shore, distance from river, temperature, and habitat types (mangrove forest, freshwater swamp, and shrubs). MAXENT prediction showed that elevation was the most influential variable with AUC (Average Under Curve) value of 0.952. Settlements with activities occurring within one kilometer from the river and those adjacent to coastal areas proved to be the highest in human conflicts with crocodiles. Key words: conflict, crocodile, human, MAXENT